Applicability of DNA traceability along the entire wine production chain in the real case of a large Italian cooperative winery. (June 2021) - Zambianchi, Sara; Soffritti, Giovanna; Stagnati, Lorenzo; Patrone, Vania; Morelli, Lorenzo; Vercesi, Alberto; Busconi, Matteo
Abstract: Wine is frequently reported as one of the most adulterated agro-food products worldwide. Among the traceability methods available, DNA is of particular interest providing the possibility to recognize uniquely the wine production cultivar/cultivars. Several studies carried out in controlled conditions (laboratory level or small production wineries) support the use of DNA in wine traceability, but the situation can change completely when moving from controlled to uncontrolled realities. In the present study, the entire production chain, in a large cooperative Italian winery, was followed, for a monovarietal (Pinot noir PDO) and a polyvarietal (Rosso Oltrepò TGI) production. Results support the feasibility of DNA traceability from grape delivering to the whole fermentation process and through the most common oenological operations as racking and filtration. The application of most aggressive methods (as the thermovinification process) can increase DNA degradation reducing but not hampering the possibility to apply DNA for traceability purposes. A different situation concerns the storage of wine in tanks, despite the controlled temperature and light conditions, or in bottles where DNA degradation continues strongly influencing the possibility to apply traceability. Highlights: First application of DNA traceability in a real large scale cooperative winery. DNA traceability is easily doable in uncontrolled conditions until musts. Standard oenological processes do not interfere with traceability. Thermovinification reduces but non hampers traceability. Storage in tanks reduce the possibility to apply DNA traceability.